LUPUS PANNICULITIS INVOLVING THE PAROTID/PERIPAROTID REGIONS AND BREAST; A RARE PRESENTATION - Janjua, Shahbaz A.; McColl, Ian; Thomas, Jayakar (Journal of Ayub Medical College Abbottabad, 2004)
Kaposi first described lupus erythematosus panniculitis, also known as lupus panniculitis and lupus profundus, in 1869, and Arnold established it as a subtype of lupus erythematosus in 1956.1 It is a chronic relapsing panniculitis that occurs in about 1 to 3% of patients with cutaneous lupus erythematosus and it is characterized by the development of deeply situated subcutaneous nodules and/or plaques with a predilection for the upper arms, face, shoulders and buttocks.2,3 Rarity of involvement of the lower extremities distinguishes this condition from other forms of panniculitis, particularly erythema nodosum4 Lupus panniculitis may occur as a separate entity or in association with systemic lupus erythematosus or discoid lupus erythematosus.5 As the serological abnormalities are rare, the diagnosis is based on the clinical and histological findings. Antimalarials and corticosteroids are the mainstay of treatment but their real worth is still to be determined.4 We report a chronic case of lupus pannicultis in a middle-aged woman affecting her face including the left parotid/periparotid region, left upper arm and right breast. Breast and parotid/periparotid areas are less commonly involved in lupus panniculitis.6,7 To the best our knowledge, only a few cases of lupus panniculitis involving the parotid/periparotid region have previously been reported in the literature